A GIS‐based spatial index of feedstock‐mixture availability for anaerobic co‐digestion of Mediterranean by‐products and agricultural residues. (22nd March 2018) - Valenti, Francesca; Liao, Wei; Porto, Simona MC
Abstract: Biogas obtained from the anaerobic digestion of biomasses has increasingly been considered a feasible alternative to energy production from fossil fuel because of the possible advantages derived from both the reduction of the environmental burden and the reuse of by‐products and agricultural residues. Italy is the third largest biogas producer in the world after China and Germany, but the biogas sector in southern Italy, especially in Sicily, is still developing. The objective of this study was to contribute to the sustainable development of the biogas sector in Sicily by developing a method for the localization of geographical areas suitable for biogas production. First, a feedstock mixture found in previous research studies (which investigated several mixes of main agricultural residues and by‐products available in Sicily for the enhancement of biogas production in terms of methane content) was used to evaluate each feedstock territorial distribution in a study area. Then a GIS‐based model for the computation of a spatial index of feedstock‐mixture availability, i fm_a, was developed. The computed spatial index was applied on a GIS map to investigate the availability of the feedstock mixture in the area under study. The results of the territorial analyses obtained by applying the index showed the geographical areas suitable for the development of new biogas plants. The results of this study could be helpful in reducing the significant transport costs of each feedstock as well as the environmental impact of biogas production. In this regard, the results are in line with the policy priorities of the Europe 2020 strategy, which aims to valorize by‐products and agricultural residues through their reuse. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd